The usefulness of social media analysis within scholarly publications: a study of first-tier tourism journals - Antonio Peláez-Verdet; Manuel Ferrera-Blasco (Tourism & Management Studies)
The introduction of social network techniques in scholarly research analysis has driven a better understanding of the main authors and their debates. These tools have improved the traditional bibliographic models considerably. The present analysis applied the centrality indicators from social network analysis to first-tier journal articles (index: Journal Citation Reports (SSE)). The results revealed that journal specialization within the tourism theme is consistently in line with their editorial line, with minor issues detected. When it comes to academic debate, however, the topics are not concentrated homogenously. The authors at the center of the debate are not always the most prolific, yet it turns out that co-authoring helps them to gain central positions within the debate